Doing cultural studies in rough seas: the COVID-19 ocean multiple. Issue 2 (4th May 2021) - Probyn, Elspeth
ABSTRACT: This article seeks to demonstrate what a conjunctural analysis of the oceanic manifestation of COVID-19 might look like. While the ocean has seemingly remained on the periphery during the ongoing pandemic, the marine has nevertheless been deeply affected as a space of more-than-human connection. As we know, it was at a seafood market (The Huanan Seafood Market) that the first signs of the virus allegedly emerged – an event that propelled the circulation of disgust and racism that was to follow. I take three sites: Botany Bay, Sydney; the Ruby Princess cruise ship; and the effect of COVID-19 on fish supply chains and the lives and livelihoods of fishers especially in the global south. I draw on John Clarke's argument that 'tracing the different dynamics and forces that come together to constitute the conjuncture is a substantial challenge', and Meaghan Morris' call for site-specific thinking in cultural studies. This is, I argue, a time for messy digging in the swamp of the pandemic if we are to find thin threads of hope for our more-than-human world, and our discipline.